Optimizing shape characteristics of high refractive index particles to improve forward scattering. (October 2019) - Barreda, A.I.; Gutiérrez, Y.; Alcaraz de la Osa, R.; Moreno, F.; González, F.
Highlights: Enhance the Zero-Backward condition for improving solar cells efficiency. Forward scattered intensity for different geometries of silicon nanoparticles. The most promising geometries are parallelepipeds and cylinders. Extinction efficiency at the Zero-Backward condition is a suitable figure of merit. Abstract: High Refractive Index Dielectric nanoparticles have been proposed as an alternative to metallic ones due to their low losses and their directionality properties. In particular, at the Zero-Backward condition (near Zero-Forward condition), incident radiation is forward (backward) scattered being null (almost null) in the backward (forward) direction. Both Scattering Directionality Conditions have been evidenced experimentally for several geometries, including spherical nanoparticles. In this work, we numerically analyze the amount of scattered electromagnetic energy in the forward region under the Zero-Backward condition for different geometries of isolated High Refractive Index silicon nanoparticles. The study is focused on cylinders, ellipsoids and parallelepipeds, being the latter the most promising one. To establish comparisons, the volume of all of the geometries has been kept constant and equal to that of a spherical particle of radius 150 nm, for which Kerker conditions hold in the near-infrared. This research looks at those applications where high efficiency forward scattering is required, for instance, in photovoltaic devices.